The Transformation of Design Knowledge in the Age of Artificial Intelligence (Journal of Interior Design and Academy, 2026)
The integration of artificial intelligence (AI) into design processes fundamentally transforms the nature of design knowledge. Traditional approaches often conceptualize the design process through a binary framework of black-box and glass-box metaphors. However, these metaphors are insufficient to capture the simultaneous, interactive, and permeable nature of knowledge production in AI-assisted design. Accordingly, this study examines the transformation of design knowledge in the AI era from an epistemological perspective, aiming to reconsider the processes that shape both knowledge and its production. The research employs a theory-building methodology situated within qualitative research paradigms. The findings reconceptualizes design knowledge not as a linear production chain, but as a multi-layered knowledge ecosystem in which human intuition, AI inference, and explainability layers are interwoven. In this respect, the study distinguishes itself from existing research by emphasizing a multi-layered knowledge ecosystem, moving beyond the black-box/glass-box duality, and proposing a third epistemological approach.
Keywords: Design knowledge; epistemology; black-box; glass-box; explainable AI